Network and traffic engineering in emerging distributed computing applications - Abawajy, Jemal H.; Pathan, Mukaddim; Rahman, Mustafizur; Pathan, Al-Sakib Khan; Deris, Mustafa Mat (Premier reference source, 2013)
"This book focuses on network management and traffic engineering for Internet and distributed computing technologies, as well as present emerging technology trends and advanced platforms" - Provided by publisher